Spatial analysis of exposure to traffic-related air pollution at birth and childhood atopic asthma in Toronto, Ontario. (July 2015) - Shankardass, K.; Jerrett, M.; Dell, S.D.; Foty, R.; Stieb, D.
Abstract: Findings from the Toronto Child Health Evaluation Questionnaire (TCHEQ) study indicate that early childhood exposure to traffic-related air pollution (TRAP) is related to the onset of atopic childhood asthma. To test this hypothesis further, we investigated whether spatial patterns in the birth neighbourhood of TCHEQ subjects with atopic asthma (136 of 909 schoolchildren in grades 1–2) could be explained by TRAP and other risk factors. If a causal relationship exists between early childhood residential exposure to TRAP and the development of atopic asthma, we hypothesise that (1) clusters of current asthma should exist around the place of residence at birth, and (2) accounting for residential concentrations of TRAP at birth should explain some of the autocorrelation. Several high asthma clusters were observed. Adjusting for TRAP completely explained one cluster; elsewhere, clusters were only partially explained by TRAP. Findings suggest that exposure during early childhood to TRAP in Toronto is an important contributor to the development of the atopic asthma phenotype and reveal the likely importance of other risk factors not measured in the fixed effects of the model. Highlights: Several high asthma clusters were observed around the neighbourhood of birth. Traffic related pollution exposure at birth partly explained this spatial variation. Macro- and meso-social factors in early life appear to contribute to patterns of atopic childhood asthma.